2012
DOI: 10.1002/adma.201202195
|View full text |Cite
|
Sign up to set email alerts
|

High‐Hole‐Mobility Field‐Effect Transistors Based on Co‐Benzobisthiadiazole‐Quaterthiophene

Abstract: High-mobility organic thin film transistors based on a benzobisthiadiazole-containing polymer are presented together with their morphological and optical properties. A very tight packing pattern of "edge-on" orientated polymer chains is observed in their thin films after annealing, and the hole mobility of this polymer is up to 2.5 cm(2) V(-1) s(-1) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 28 publications
2
97
0
1
Order By: Relevance
“…Although the polymer contains BBT rings that acts as strong acceptor units, the devices for P1 showed predominantly p-type characteristics with good carrier mobilities of 0.02 cm 2 V 1 s 1 , threshold voltages of 9 and on/off ratios of 10 4 . These results are consistent with exclusive p-type behavior in similar polymers [14]. Since the donor unit proportions are decreased in P2, it is expected that the charge carrier type would change in P2.…”
Section: Ofet Device Characteristicssupporting
confidence: 87%
See 1 more Smart Citation
“…Although the polymer contains BBT rings that acts as strong acceptor units, the devices for P1 showed predominantly p-type characteristics with good carrier mobilities of 0.02 cm 2 V 1 s 1 , threshold voltages of 9 and on/off ratios of 10 4 . These results are consistent with exclusive p-type behavior in similar polymers [14]. Since the donor unit proportions are decreased in P2, it is expected that the charge carrier type would change in P2.…”
Section: Ofet Device Characteristicssupporting
confidence: 87%
“…However, there is a wide variety of choice for the acceptor units. We have focused on benzo[1,2-c:4,5-c']bis- [1,2,5]thiadiazole (BBT), which is a quinoidal heterocycle with hypervalent sulfur atoms [11][12][13][14][15][16][17][18][19]. This system has a high electron affinity and forms a unique molecular network, resulting in excellent building blocks for n-type semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…The structural features of these polymer layers seem to be divers and a high charge-carrier mobility is attributed to structures with an enhanced π-π stacking [20], increased intermolecular interactions [19], (edge-on) lamellar arrangements [74,75], high film crystallinity [76,77] and/or molecular orientation/order [1,76,78]. While many open questions, thus, still remain, it is clear from the above that experimental data point towards an anisotropic nature of charge transport in macromolecular semiconductors.…”
Section: Influence Of Molecular Conformation Order and Chain Intercomentioning
confidence: 99%
“…We have focused on benzo [1,2-c:4,5-c']bis [1,2,5]thiadiazole (BBT) as the core structure, which has a high electron affinity based on a quinoidal structure with hypervalent sulfur atoms ( Figure 1). [35][36][37][38][39][40][41] Recently, Yamashita et al reported a high electron mobility of 0.77 cm 2 V −1 s −1 and the high ambient-stability for the vacuum-deposited devices based on the compound with BBT and p-(trifluoromethylphenyl)thiophene (compound 1), although its solubility was apparently low. 42 The para-(trifluoromethylphenyl)aryl group definitely affords good n-type semiconducting properties.…”
Section: Introductionmentioning
confidence: 99%